EKONOMIKA TÁLIM BAǴDARÍNÍŃ TALABALARÍ UShÍN RÁSMIY KOMMUNIKACIYANÍŃ ÁHMIYETI - Esanova, A.Z. (SCIENCE and SOCIETY, 2025)
This article tells future economists about the importance of formal communication, its practical benefits and skills, and ways to develop formal communication.
Keywords: communication; formal communication; economics student; professional competence; communication culture